The Role of Preventive Healthcare and Lifestyle in Combating Chronic Diseases - Saumya Mishra,; Dr. Sukanya Chakravorty, (The Bioscan, 2026)
Chronic diseases, including cardiovascular conditions, diabetes, cancers, and respiratory disorders, represent a significant global health challenge, accounting for 70% of worldwide deaths and imposing substantial burdens on healthcare systems and individuals. Emerging evidence underscores the transformative role of nutrition in preventing and managing these conditions, emphasizing the power of informed dietary choices in shaping health outcomes. Diets rich in antioxidants and minimally processed foods, such as the Mediterranean and Dietary Approaches to Stop Hypertension (DASH) diets, are associated with reduced risks of cognitive decline, cardiovascular disease, and diabetes. Whole grains, vegetables, fruits and nuts demonstrate protective effects against the onset and progression of chronic diseases. Conversely, ultra-processed diets contribute to increased caloric intake, weight gain, and metabolic imbalances. Physical activity and stress management further complement nutritional strategies. Regular moderate exercise for 150–300 min weekly reduces the risk of depression and obesity, while yoga, mindfulness, deep breathing and consistent sleep patterns enhance overall resilience. Preventive screenings, combined with these lifestyle interventions, significantly improve survival rates by enabling early detection and timely action. Addressing chronic diseases requires overcoming challenges such as individual variability, food accessibility, and gaps in nutritional education. Collaborative, multidisciplinary efforts are vital to advance research, implement evidence-based strategies, and promote population-wide health improvements. This synthesis reinforces the critical need for sustainable dietary habits, highlighting that even small, incremental lifestyle changes can lead to profound health benefits. It underscores the timeless proverb: “prevention is better than cure”.